Perception of Punjab Paddy Growers towards Climate Change - Brar, Harsimranjit Singh; Sharma, Anil; Gill, Jagjeet Singh; Sharma, Surabhi (Indian Journal of Extension Education, 2017)
The study was conducted in five agro climatic zones of Punjab. One district from each zone, three blocks from each district and further one village from each block was selected randomly. Ten farmers having experience of minimum fifteen years of paddy cultivation, from fifteen villages of five zones were selected. Data was collected by using the interview schedule. More than three fourth (78.38 %) of the respondents agreed with the statement that climate change lead to more outbreak of diseases whereas 21.62 per cent of the respondents had neutral response. The quality of crop was affected due to climate change was perceived by 73.65 per cent of the respondents and very few (4.73%) had neutral response towards this statement. Statements namely paddy production is affected, affecting date of transplantation of the crop, selection of varieties to be sown, delaying crop maturity, leading to new weeds infestation, more outbreak of diseases, crop quality affected, net income from the crop were having mean score 2.72, 2.32, 2.34, 2.33, 2.10, 2.78, 2.69 and 2.70 respectively and were found to be significant with the perception of the farmers regarding climate change.
Keywords: Paddy Growers; Climate Change; Perception; Punjab State; Farmers Response